A autonomia enquanto proposição fundamental da ética prudencial de epicuro - Zmijewski, Marcos Adriano (2023)
The goal of this thesis is to present the meaning and the connexions between the main ethical propositions of Epicurus. The core of the thesis has as its aim to demonstrate under which terms the philosopher conceived the conquest of ethical autonomy, by which he understands the human skill of governing one’s own life reaching the fulfilment of one’s nature and, within self-acceptance and in freedom, to live joyfully. The thesis is divided into two parts: i) in the first one, it is presented the links between philosophia, phrónêsis, pleasure and desire, under the assumption that Epicurus had founded his ethics in a strictly naturalistic basis, without forging abstract, utopian or even incompatible parameters with nature and human needs; ii) in the second one, the core of the studies rely on what Epicurus consider as principles of good living (which are: autárkeia, philía and láthe biósas). By analysing the meaning that each principle assumes in the epicurean doctrine (as well as the intersections with other concepts, such as autodidaxía, liberty and justice), the thesis aims to demonstrate how Epicurus made the wellness of the individual precede the needs of the polis in his ethos. The analysis is based on Epicurus remaining writings (epistles, maxims and sentences), in the texts of his disciples and also in the works of tradition (specially the critical tradition) that mention the issues approached in this thesis.